1989
DOI: 10.1016/0014-5793(89)81606-0
|View full text |Cite
|
Sign up to set email alerts
|

Animal and plant mitochondria contain specific thioredoxins

Abstract: Thioredoxins have been purified from pig heart and potato tuber mitochondria which differ in chromatographic behaviour, enzyme activating capacity, and slightly higher molecular mass (M,= 12 500) from the major thioredoxin(s) present in mitochondria-free fractions of the same tissue. Both mt-thioredoxins can serve as hydrogen donor for E.&i ribonucleotide reductase but only the plant protein activates spinach chloroplast NADP malate dehydrogenase in vitro. Mitochondrial target enzymes specifically activated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 32 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…This is consistent with AOX reduction being mediated by a thioredoxin-or glutaredoxin-based enzyme system, both of which use NADPH (Holmgren, 1989). Components of each of these systems have been identified in plant mitochondria, but, as yet, potential specific function(s) have not been identified (Bodenstein-Lang et al, 1989;Rasmusson and Maller, 1990). It is interesting that reduced thioredoxin from Esckerickiu coli can reduce soybean AOX in insideout submitochondrial particles (J.N.…”
Section: +Aamentioning
confidence: 57%
“…This is consistent with AOX reduction being mediated by a thioredoxin-or glutaredoxin-based enzyme system, both of which use NADPH (Holmgren, 1989). Components of each of these systems have been identified in plant mitochondria, but, as yet, potential specific function(s) have not been identified (Bodenstein-Lang et al, 1989;Rasmusson and Maller, 1990). It is interesting that reduced thioredoxin from Esckerickiu coli can reduce soybean AOX in insideout submitochondrial particles (J.N.…”
Section: +Aamentioning
confidence: 57%
“…On the other hand, the reaction is of major interest in connection with the existence of specific mitochondrial thioredoxins [5,6]. We suggest that a-ketoaciddependent thioredoxin reduction is an integral part of the thioredoxin cycle in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been prompted by our earlier observation of specific mitochondrial thioredoxins [5,6], which are in search of a function.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports indicated that plant mitochondria also contain at least one thioredoxin (12,92), but no cDNA sequence has been unambiguously shown to code for a transit peptide that targets the mitochondrial compartment. Similarly, no plant mitochondrial NTR sequence has yet been isolated.…”
Section: Thioredoxin Systems In Mitochondriamentioning
confidence: 99%